Komunikasi Persuasif Guru Bahasa Kaili dalam Meningkatkan Keterampilan Berbahasa Kaili pada Siswa di SD Unggulan Putra Kaili Permata Bangsa - Rasyid, Mohammad Amien Rais; Fadhliah; Nurhaidar (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
The purpose of this research is to find out Kaili language teacher's persuasive communication in improving Kaili language skills among students at SD Unggulan Putra Kaili Permata Bangsa. This type of research is qualitative descriptive research. Using Hafied Cangara persuasive communication method, feard appeal, emotional appeal, reward appeal, motivational appeal and humorius appeal. The subjects in this research were teachers who taught Kaili language. The qualitative descriptive used in this research is data reduction, display and data verification. Data collection techniques were carried out using observation, interviews and literature studies. The results of this research indicate that several techniques for presenting persuasive communication messages used in the teaching and learning process between teachers and students at SD Unggulan Putra Kaili Permata Bangsa are effective for teachers to use in persuading students to develop students' Kaili language skills because this message presentation technique is easily accepted by students at SD Unggulan Putra Kaili Permata Bangsa. Meanwhile, the inhibiting factor for students in using Kaili language is the lack of the role of parents/guardians in getting students used to using Kaili language.